Rapid standardized operating rooms (RAPSTOR) in thyroid and parathyroid surgery - Hannah Ernst; Leigh Sowerby; Axel Sahovaler; Danielle Macneil; Anthony Nichols; John Yoo; Richard Hilsden; Julie Strychowsky; Kevin Fung (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Objective To evaluate the impact of a high efficiency rapid standardized OR (RAPSTOR) for hemithyroid/parathyroid surgery using standardized equipment sets (SES) and consecutive case scheduling (CCS) on turnover times (TOT), average case volumes, patient outcomes, hospital costs and OR efficiency/stress. Methods Patients requiring hemithyroidectomy (primary or completion) or unilateral parathyroidectomy in a single surgeon’s practice were scheduled consecutively with SES. Retrospective control groups were classified as sequential (CS) or non-sequential (CNS). A survey regarding OR efficiency/stress was administered. Phenomenography and descriptive statistics were conducted for time points, cost and patient outcome variables. Hospital cost minimization analysis was performed. Results The mean TOT of RAPSTOR procedures (16 min; n = 27) was not significantly different than CS (14 min, n = 14) or CNS (17 min, n = 6). Mean case number per hour was significantly increased in RAPSTOR (1.2) compared to both CS (0.9; p < 0.05) and CNS (0.7; p < 0.05). Average operative time was significantly reduced in RAPSTOR (32 min; n = 28) compared to CNS (48 min; p < 0.05) but not CS (33 min; p = 0.06). Time to discharge was reduced in RAPSTOR (595 min) compared to CNS (1210 min, p < 0.05). There was no difference in complication rate between all groups (p = 0.27). Survey responses suggested improved efficiency, teamwork and workflow. Furthermore, there is associated decrease in direct operative costs for RAPSTOR vs. CS. Conclusion A high efficiency standardized OR for hemithyroid and parathyroid surgery using SES and CCS is associated with improved efficiency and, in this study, led to increased capacity at reduced cost without compromising patient safety. Level of evidence Level 2. Graphical abstract